The deciding factors for expatriate purchase of property in Malaysia - Amer Adel, Shahad (2019)
In an attempt to attract more foreigners residing in Malaysia, the government has developed Malaysia My Second Home (MM2H) scheme which enable foreigners to buy freehold properties. The aim of MM2H is to boost local economy of Malaysia through attracting financial-independent foreigners to spend a luxurious life in this country. Increased foreign direct investment in real estate properties and businesses, cash flow in fixed deposits as well as other spending in Malaysia are the potential advantages of long stay schemes in Malaysia Despite the importance of foreigner’s long stay scheme to the economy of Malaysia, in the current literature there are not many studies investigating the factors that attribute to decision making of expatriate regarding buying house in Malaysia, particularly in Kuantan. Therefore, the objective of this study is to investigate the effect of property attribute including house price, house type, house finishing such as kitchen cabinet, house design, the age of the house, property view such as house exterior feature, house layout plan, land area and property surrounding such as proximity to facilities, education area, work place and etc. on expatriate purchase of house in Kuantan Malaysia. Quantitative method in this study and 500 data was collected through self-administrated questionnaire. SPSS Software version 21 was used to analyze the data. The result of data analysis showed that all property attribute, property view and property surrounding have an effect on house purchase intention of Middle East individuals in Malaysia. Moreover, the findings of this study showed that most of the people believed that environment quality, security, proximity to facilities, view of the housing area such as north or south direct, house layout plan, house price, house title, house finishing, traffic congestion and land area are the most important issues that Middle East people consider while buying house in Malaysia.